2020
DOI: 10.1186/s40854-020-0171-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of E-banking channels and market share in developing countries

Abstract: There is fierce global competition within the banking industry. Therefore, banks endeavor to grow and strive to increase their market share. We analyzed the effect of developing innovative channels of presenting bank services on banks' market share. The statistical population of this research was Shahr bank's central headquarter and its branches in Tehran, Iran. We developed questionnaires for gathering the data. The validity and reliability of the scales were tested by EFA, CFA, experts' opinion, and Cronbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 50 publications
1
30
0
1
Order By: Relevance
“…For example, training, or publishing some videos on the Bank's website or sending personal emails to it's customers, in order to increase there knowledge about how to learn about and use E-Banking channel services safely. Particularly, it is crucial to approach different generations and to avoid there losing cost and time by travelling to banks' branches (Wang et al 2020;Nazaritehrani and Mashali 2020). It is true that a previous study proved that Trust should be earned by providing the highest quality traditional banking services (for example, ATM, Internet Banking, Mobile Banking, and Application Banking) at the physical bank's branches (offline banking) (Chaouali et al 2016;Alhassany and Faisal 2018;Chen et al 2017), to build a reputation and a respectable image and consequently attract existing, and potential customers into the system.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…For example, training, or publishing some videos on the Bank's website or sending personal emails to it's customers, in order to increase there knowledge about how to learn about and use E-Banking channel services safely. Particularly, it is crucial to approach different generations and to avoid there losing cost and time by travelling to banks' branches (Wang et al 2020;Nazaritehrani and Mashali 2020). It is true that a previous study proved that Trust should be earned by providing the highest quality traditional banking services (for example, ATM, Internet Banking, Mobile Banking, and Application Banking) at the physical bank's branches (offline banking) (Chaouali et al 2016;Alhassany and Faisal 2018;Chen et al 2017), to build a reputation and a respectable image and consequently attract existing, and potential customers into the system.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Again, a study comprised 182 respondents including managers, deputies, and experts of Shahr bank from its branches in Tehran, Iran to formulate a regression model to show the effect of the development of new banking services i.e. internet banking, telephone banking, mobile banking, ATM development and Point of Sale Terminals on a bank's market share (Nazaritehrani & Mashali, 2020). Moreover, a comparative study explores 22 problems of e-banking and ranked the significant problems with the help of Standardized Canonical Discriminant Function Coefficients among the new users at Thiruvananthapuram District in India by collecting data from the customers of SBI and Corporation bank in Thiruvananthapuram district (Dhanya & Velmurugan, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…e adoption of innovation in the Banking Sector has facilitated transactions and business worldwide. Internet banking structures, such as electronic checks payment system, Automatic Teller Machines (ATMs), credit visa, debit and master cards, mobile banking applications, etc., have transformed the world where clients may be able to purchase and sell goods and services, and also can make money transactions through the use of Internet [7,14,17,18]. Chai et al [5] have confirmed that the introduction of Internet banking has increased efficiency, effectiveness, and productivity levels in the banking industry.…”
Section: Eoretical Review Of the Literature And The Conceptualmentioning
confidence: 99%
“…Most of the studies of Internet banking services or innovation have been performed in economically developed nations [10][11][12][13]. Furthermore, the authors of [14] argued that developing countries might radically differ from developed countries when exploiting and exerting innovation. It is useful and necessary to carry out a study on the relationship between Internet banking and bank performance in developing countries.…”
Section: Introductionmentioning
confidence: 99%